Bioimpedance in 7-Year-Old Children: Validation by Dual X-Ray Absorptiometry - Part 2: Assessment of Segmental Composition - Luque, Veronica; Escribano, Joaquin; Zaragoza-Jordana, Marta; Rubio-Torrents, Carmen; Ferré, Natalia; Gispert-Llaurado, Mariona; Closa-Monasterolo, Ricardo (Annals of nutrition and metabolism, 2014)
Aim: Segmental body composition in children was assessed using the bioimpedance analyzer (BIA) TANITA BC-418 and compared with dual-energy X-ray absorptiometry (DXA) values. Methods: A cross-sectional validation study in which 7-year-old children from the Spanish subsample of the EU Childhood Obesity Project were assessed through anthropometry, BIA and DXA. Main outcome measures were fat and lean masses of the trunk, left arm and left leg (in kg) assessed through BIA direct outputs (BIA outputs ) and DXA. Predictive equations for the composition of each segment were derived from raw impedance and anthropometric measurements; results obtained from these predictive equations (BIA regressions ) were also compared to DXA. Results: One hundred seventy-one (84 boys) 7-year-old children were studied. BIA outputs and DXA results showed small differences for leg lean mass (6.5%) and high differences for trunk fat and trunk lean masses (>30%). BIA regressions results showed differences of about 20% for trunk fat mass, 1.5% for trunk lean mass and 3.7% for leg lean mass compared to DXA. Conclusions: Segmental body composition measures predicted by internal algorithms of the TANITA BC-418 were not valid for clinical or epidemiological use, except for leg lean mass. The assessment of segmental composition was improved using our own predictive equations combining segmental-specific anthropometric measurements with segmental impedances.